A Developmental Study of Junior High School Mathematics Instructional Media Guided from Humanity-Value of Learning Model (MPNK) to Prevent Juvenile Delinquency - Murdiana, I Nyoman; Lefrida, Rita (JPP (Jurnal Pendidikan dan Pembelajaran), 2017)
Abstract: The Research and Development study aimed to develop a instructional media for math lesson using valid, practical, and effective humanity-value teaching model to prevent juvenile delinquency. To achieve the objective, the prototypical study was conducted using 3 phase development, namely (1) early assessment phase or front-end analysis, (2) the development phase consisting of expert validation and tryout I, and (3) the evaluation phase through tryout II using a quasi experiment design with anacova data analysis. The result from the first year development (2015) was the instructional media for junior high school using a valid humanity-value teaching model to prevent various kinds of juvenile delinquency. The products developed from the current research were in the form of lesson plan, teacher’s book, student book, and student worksheets. The products were in the form of draft of the instructional set which was valid.Keywords: instructional media, junior high school, mathematics, MPNK modelAbstrak: Penelitian ini merupakan penelitian pengembangan untuk menghasilkan perangkat pembelajaran matematika SMP berpandu Model Pembelajaran Nilai Kemanusiaan (MPNK), yang valid, praktis, dan efekktif guna mencegah kenakalan remaja.Untuk mencapai tujuan tersebut, maka jenis penelitian yang digunakan adalah prototypical studies melalui tiga tahap pengembangan. Tiga tahap tersebut yakni: (1) fase hulu hilir, (2) fase pengembangan melalui kegiatan validasi oleh pakar dan kegiatan uji coba I; (3) fase penilaian melalui kegiatan uji coba II dengan rancangan “Quasi- Expriment” dan datanya dianalisis dengan Anacova. Hasil yang telah diperoleh untuk pengembangan tahun I (2015) adalah produk perangkat pembelajaran matematika SMP berpandu MPNK, yang valid dalam rangka mencegah berbagai bentuk kenakalan remaja. Produk yang telah diperoleh dari hasil penelitian ini berupa Rencana Pelaksanaan Pembelajaran (RPP), Buku Guru, Buku Siswa, dan Lembar Kerja Siswa. Produk tersebut berupa Draft Perangkat Pembelajaran yang telah memenuhi kualitas valid.Kata kunci: matematika, model MPNK, perangkat pembelajaran, SMP